THU0477 Canakinumab Improves Health-Related Quality of Life (HRQOL) and Daily Functioning in Systemic Juvenile Idiopathic Arthritis (SJIA) Patients. (23rd January 2014) - Quartier, P.; Ruperto, N.; Wulffrat, N.; Brunner, H.; Brik, R.; McCann, L.; Foster, H.; Frosch, M.; Gerloni, V.; Harel, L.; Len, C.; Houghton, K.; et al.
Abstract : Background: Efficacy and safety of canakinumab (CAN), a selective, fully human, anti-interleukin-1β monoclonal antibody, in SJIA is supported by the results of 2 phase III trials. In Trial 1 (4-Wk, randomized placebo (PBO)-controlled 1 ) significantly more CAN than PBO group patients (pts) achieved an aACR-Ped30 response. In Trial 2 (open-label CAN-treatment [Part 1] followed by a randomized PBO-controlled withdrawal phase [Part2] 1 ), CAN allowed successful reduction/ discontinuation of steroids and significantly prolonged time to flare, with a safety profile consistent with expectations for a biologic agent 1 . Although pts with SJIA suffer from a significant impairment in their HRQoL and functioning 2, little is known on the effect of CAN on functional ability and HRQoL. Objectives: To report the patient-reported functional ability and HRQoL outcomes from the Phase III program. Methods: In both studies, functional ability was assessed by the Childhood Health Assessment Questionnaire (CHAQ © ), HRQoL by Child Health Questionnaire–Parent Form (CHQ-PF50 © ) for physical ability and psychosocial health status. The CHQ-PF50 is a generic self-administered instrument designed to capture the physical, emotional, and social components of the health status of children. The CHAQ © contains a disability dimension with 20 multiple choice questionnaire concerning difficulty in performing 8 common activities of daily living as well as a parent's or patient's assessment of the child overall well-being and pain intensity on VAS (0–100 mm). Results: In Trial 1, improvement from baseline (BL) CHAQ disability index scores for pts treated with a single injection of CAN vs PBO was observed at Day 15 with further improvement at Day 29 and overall, CAN group had an estimated 0.69 improvement vs PBO in the least square mean (LSM) change from BL (p=0.0002) which was 3.6 x the MCID of -0.19 3 . At Day 29, significant improvements in estimated difference in LSM from BL for VAS pain intensity (-41.86, p<0.0001), and over time in estimated difference in LSM from BL for CHQ-PF50 physical (PhS) (+12.1, p=0.0012) and psychosocial (PsS) (+7.3, p=0.0017) scores were observed for CAN vs PBO. In Trial 2, similar improvements were observed from BL to end of Part 1 with mean improvements of -1.0 in CHAQ disability score, +21.6 for CHQ-PF50 PhS and +9.1 for the CHQ-PF50 PsS, respectively. During Part 2, both CHQ-PF50 scores improved for CAN group (Table). Conclusions: CAN treatment in pts with SJIA resulted in rapid, sustained, and clinically relevant improvements in pts' HRQoL, pain, and disability with marked improvement observed by Wk 2 of treatment. These results support the meaningful and rapid improvement of SJIA patients with CAN. References: Ruperto N et al. N Engl J Med 2012;367:2396-406. Gutiérrez-Suárez R et al. Rheumatology 2007;46 (2): 314-320. Brunner HI et al. J Rheumatol 2005; 32:150-61. Disclosure of Interest: P. Quartier Grant/research support from: Abbot, Novartis, Pfizer, Consultant for: Novartis, Servier, Swedish Orphan Biovitrium, Speakers bureau: Abbot, BMS, Novartis, Pfizer, Roche, N. Ruperto Grant/research support from: Abbot, Astra Zeneca, Bristol Myers and Squibb, Centocor research & development, Eli Lilly and company, "Francesco Angelini" s.p.a, Glaxosmith & Kline, Italframaco, Merck Serono, Novartis, Pfizer, Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, Wyeth, Speakers bureau: Abbott, Bristol Myers Squibb, Astellas, Boehringer, Italfarmaco, MedImmune, Novartis, Pfizer, Roche, N. Wulffrat Grant/research support from: Roche, Abbot, Consultant for: Novartis, Pfizer, Roche, H. Brunner Consultant for: Consultation agreement with <10, 000/ year, Coordinating center contract with payment to CCCHMC, R. Brik: None Declared, L. McCann: None Declared, H. Foster: None Declared, M. Frosch: None Declared, V. Gerloni: None Declared, L. Harel: None Declared, C. Len: None Declared, K. Houghton: None Declared, R. Joos: None Declared, D. Kim Employee of: Novartis Pharmaceuticals Corporation, K. Abrams Employee of: Novartis Pharmaceuticals Corporation, K. Lheritier Employee of: Novartis Pharma AG, J. Ricci Shareholder of: Novartis, Consultant for: Novartis, A. Martini Grant/research support from: Abbot, Astra Zeneca, Bristol Myers and Squibb, Centocor research & development, Eli Lilly and company, "Francesco Angelini" s.p.a, Glaxosmith & Kline, Italframaco, Merck Serono, Novartis, Pfizer, Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, Xoma, Wyeth, Speakers bureau: Abbott, Bristol Myers Squibb, Astellas, Boehringer, Italfarmaco, MedImmune, Novartis, Pfizer, D. Lovell Grant/research support from: National Institutes of Health, Consultant for: Astra-Zeneca, Centocor Inc, Wyeth, Amgen, Bristol-Meyers Squibb, Abbot, Regeneron, Hoffmann-La Roche Inc, Novartis, UBC, Forest research Med, Employee of: Cincinnati Children's Hospital Medical Center, Speakers bureau: Wyeth